2013
DOI: 10.1136/bmjopen-2012-001788
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of handheld rebound tonometry with Goldmann applanation tonometry in children with glaucoma: a cohort study

Abstract: ObjectiveTo test agreement of two methods to measure intraocular pressure (IOP): rebound tonometry (RBT) and gold standard Goldmann applanation tonometry (GAT) in children with glaucoma.DesignObservational prospective cohort study.SettingTertiary paediatric glaucoma clinic at a single centre.Participants102 individuals attending a paediatric glaucoma clinic, mean (SD) age 11.85 (3.17), of whom 53 were male.Primary and secondary outcome measuresIntraocular pressure, central corneal thickness, child preference f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 27 publications
2
20
0
2
Order By: Relevance
“…Through literature review, many investigators[3101112131415161718] have evaluated the application of rebound tonometer ICARE and compared with other portable tonometry devices, such as the Tono-Pen XL (Medtronic Solan, FL, USA), or the Perkins tonometer (Haag-Streit), as well as the GAT (Haag-Streit), in both healthy children and those with glaucoma. [1518192021] With the advantage of elimination extra discomfort and anxiety caused by anesthetic medication before measurement, the rebound tonometer is well tolerated and reproducible in children, especially in younger age, even in infant. [451920212223] The traditional applanation tonometry by direct contact the cornea will require patient's cooperation.…”
Section: Discussionmentioning
confidence: 99%
“…Through literature review, many investigators[3101112131415161718] have evaluated the application of rebound tonometer ICARE and compared with other portable tonometry devices, such as the Tono-Pen XL (Medtronic Solan, FL, USA), or the Perkins tonometer (Haag-Streit), as well as the GAT (Haag-Streit), in both healthy children and those with glaucoma. [1518192021] With the advantage of elimination extra discomfort and anxiety caused by anesthetic medication before measurement, the rebound tonometer is well tolerated and reproducible in children, especially in younger age, even in infant. [451920212223] The traditional applanation tonometry by direct contact the cornea will require patient's cooperation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the IOP measured by rebound tonometry tended to be higher (mean, 1.92 ± 3.29 mm Hg; 95% limit of agreement, −4.52 to 8.37 mm Hg), this difference did not vary based on central corneal thickness (CCT, age, axial length, or spherical equivalent. 29 In contrast, Dahlmann-Noor et al 30 found poor agreement between the 2 methods when tested in children.…”
Section: Intraocular Pressurementioning
confidence: 98%
“…Проблема исследования офтальмотонуса у детей с врождённой глаукомой также широко обсуждается, однако, главным образом, в за-рубежной литературе [21,24,30,38,47]. Так, M.R.…”
Section: Doi: 1017816/ov9323-31unclassified
“…Вместе с тем A.H. Dalhmann-Noor et al (2013) справедливо считают, что исследо-вание фактора резистентности роговицы и кор-неального гистерезиса не является рутинной процедурой и практически неприменимо у ма-леньких детей. Авторы также доказали, что Icare завышает результаты измерения относительно тонометра Гольдмана, причём расхождение ре-зультатов измерения закономерно увеличивается с ростом ЦТР [21].…”
Section: Doi: 1017816/ov9323-31unclassified